Effect of green Coffea arabica L. seed oil on extracellular matrix components and water-channel expression in in vitro and ex vivo human skin models - Velazquez Pereda, Maria Del Carmen; Dieamant, Gustavo de Campos; Eberlin, Samara; Nogueira, Cecilia; Colombi, Debora [UNESP]; Di Stasi, Luiz Claudio [UNESP]; Queiroz, Mary Luci de Souza (Wiley Periodicals, Inc, 2009)
Background Green Coffea arabica L. seed oil is being widely used in cosmetic formulations, although its effects on human skin cells are not clear and most observations are unpublished. Aims In this study, we evaluated the in vitro effects of green coffee (C. arabica L.) oil (GCO) on the synthesis of collagen, elastin, and glycosaminoglycans (GAG) and in the release of transforming growth factor-beta 1 (TGF-beta 1) and granulocyte-macrophage colony-stimulating factor (GM-CSF) by human skin fibroblasts. We also investigated the ability of GCO to increase aquaglycerolporins-3 (AQP-3) mRNA expression in cultured keratinocytes and human skin explants.Methods Human fibroblasts were incubated for 48 h with several GCO concentrations (3.12, 6.25, 12.5, 25.0 and 50.0 mg/mL). The levels of growth factors and extracellular matrix compounds in the culture supernatant were measured using commercial kits. To evaluate AQP-3 relative expression, using real-time reverse transcription polymerase chain reaction, keratinocytes were incubated for 3-6 h with the GCO optimal concentration of 25.0 mg/mL. Histological sections of human skin were also incubated with GCO (25.0 mg/mL) and immunostained by antiserum against AQP-3.Results Our results demonstrated that incubation with GCO produces a dose-dependent stimulation in the synthesis of collagen, elastin, and GAG, in addition to increasing the release of the growth factors TGF-beta 1 and GM-CSF. GCO also induced the expression of AQP-3 mRNA, which reached levels up to 6.5-fold higher than those of the control cultures.Conclusion The findings presented herein suggest that GCO might improve physiological balance in the skin, thus allowing the formation of new connective tissue, and preventing epidermis dryness by increasing AQP-3 levels. Taking into account the limitations of in vitro studies, it is encouraging in this context to consider CGO as an adjuvant to be used in dermocosmetic formulations. Clinical studies are in progress in our laboratory aiming to further investigate the protective effects of CGO in the skin.
Keywords: Green coffee oil; Coffea arabica L.; TGF-beta 1; GM-CSF; extracellular matrix; AQP-3